A preparation method of nanofiber cling film, product and application thereof

The nanofiber plastic wrap prepared through electrospinning technology solves the problem of difficulty in extending shelf life and maintaining taste in crispy meat paste, and achieves the effect of improving meat quality characteristics while extending the shelf life.

CN118854543BActive Publication Date: 2025-03-11GUANGDONG OCEAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410826335.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-03-11
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively extend the shelf life of crispy squids while maintaining their unique taste and meatiness characteristics.

Method used

Nanofiber plastic wrap is prepared by electrospinning technology. By mixing ingredients such as beet pectin, curcumin and hesperin, nanofiber films with excellent particle size and dispersion are prepared.

Benefits of technology

This nanofiber plastic wrap can significantly improve the chewability, hardness and staleness of crispy meat, maintain the firmness and crispness of the meat, prolong its shelf life, and also have good water solubility and antibacterial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854543B_ABST
    Figure CN118854543B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of food preservation, and specifically relates to a preparation method of a nanofiber cling film, a product obtained and an application thereof. The nanofiber cling film provided by the present invention is prepared from beet pectin solution and curcumin alcohol solution containing hesperidin by an anti-solvent method into a nanoparticle solution, and then a spinning aid is added to the nanoparticle solution to prepare a nanofiber film by electrostatic spinning technology. The nanofiber cling film prepared by the present invention has the advantages of high stability and significant antibacterial effect. The present invention applies the nanofiber cling film as a cling film to the preservation of crispy meat grass carp, which can effectively maintain the hardness, cohesion, adhesion, chewiness, resilience and elasticity of the crispy meat grass carp, maintain the unique taste of the crispy meat grass carp, and can also effectively extend the shelf life of the crispy meat grass carp, which is a more ideal crispy meat grass carp cling film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food preservation, and in particular relates to a preparation method of a nanofiber fresh-keeping film and the obtained product and application. Background Art

[0002] Electrospinning is a technology that uses a high-voltage electrostatic field to draw a polymer solution or molten polymer into nanofibers. At present, some scholars have applied electrospinning technology to the field of food preservation, using electrospinning technology to embed antibacterial activity or antioxidant activity in nanofibers, thereby producing nanofiber membranes with antibacterial activity or antioxidant activity. Using nanofiber membranes with antibacterial activity or antioxidant activity as a preservative film on fruits, vegetables and aquatic products can effectively extend the shelf life of fruits, vegetables and aquatic products.

[0003] Patent document CN106966047A discloses a method for preparing an edible nanofiber cling film, which comprises: (1) dissolving pullulan in 90-95% ethanol by volume to make the mass concentration of pullulan 16-18%, and after fully dissolved, adding carboxymethyl cellulose to make its mass concentration 1-2%, to obtain a basic spinning solution; (2) adding tea polyphenols and sodium citrate to the basic spinning solution to make the mass concentrations of tea polyphenols and sodium citrate 0.5-1% and 0.3-0.5% respectively, stirring until the solution is evenly dissolved, and standing until the bubbles completely disappear to obtain a spinning solution; (3) placing the spinning solution on an electrostatic spinning machine for spinning. Compared with the coating method, the nanofiber cling film has a better preservation effect.

[0004] Patent document CN106757464A discloses a food antioxidant cellulose acetate nanofiber cling film. The nanofiber cling film uses hydrophobic cellulose acetate as a fiber-forming matrix and utilizes the natural component tannic acid molecular structure to have dual unique properties of antioxidant and complexation with iron metal ions. CA / TA-Fe +++ Composite nanofiber film. This nanofiber cling film not only gives the functional characteristics of cellulose acetate ultrafine fiber film, but also overcomes the defects of insufficient mechanical mechanics of existing cling films, and develops a new type of antioxidant cling film.

[0005] Patent document CN108049027A discloses a preparation method and application of a composite nanofiber cling film. The composite nanofiber cling film is prepared by modifying chitosan with glutaraldehyde, compounding the modified chitosan with polyethylene oxide, polylactic acid, and a cross-linking agent into a spinning solution, and then preparing the composite nanofiber cling film by an electrostatic spinning process. The antibacterial component in the composite nanofiber cling film can destroy the cytoplasmic membrane of harmful microorganisms in contact with it, kill microorganisms, and play an antibacterial and fresh-keeping effect; at the same time, the composite nanofiber cling film has good water permeability and air permeability, will not cause fruits and vegetables to heat up and become corrupt, has high mechanical properties, and is a safe, efficient, and environmentally friendly composite nanofiber cling film.

[0006] Crisp-fleshed grass carp (Ctenopharyngodon idellus C.et V) is a freshwater fish bred by feeding common grass carp with broad beans as feed. It has the characteristics of firm, compact and crisp meat, long-cooked and delicious taste, unique taste and rich nutritional value, and is deeply loved by consumers. Crisp-fleshed grass carp has high requirements for preservation technology due to its special tissue structure and physical properties. At present, the preservation technologies such as ozone treatment, chitosan coating combined with low-temperature treatment, and gas conditioning treatment used for crisp-fleshed grass carp are not obvious. Therefore, researching and developing a preservation method that can maintain the unique taste of crisp-fleshed grass carp and significantly extend the shelf life of crisp-fleshed grass carp is still a difficulty in current research. Summary of the invention

[0007] The purpose of the present invention is to provide a cling film for crispy grass carp, specifically to provide a method for preparing a nanofiber cling film and the obtained nanofiber cling film. The present invention applies the nanofiber cling film as a cling film to the preservation of crispy grass carp. Studies have found that the nanofiber cling film can effectively increase the chewiness, hardness, adhesiveness and other properties of the crispy grass carp meat, can well maintain the firmness and crispness of the crispy grass carp meat, maintain the unique taste of the crispy grass carp, and can effectively extend the shelf life of the crispy grass carp. It is a relatively ideal cling film for crispy grass carp.

[0008] The present invention provides a method for preparing a nanofiber cling film, comprising the following steps:

[0009] Step S1. dissolving beet pectin in distilled water and stirring to obtain a beet pectin solution;

[0010] Step S2. Add curcumin and hesperetin into anhydrous ethanol and stir evenly to obtain a curcumin alcohol solution containing hesperetin;

[0011] Step S3. The beet pectin solution obtained in step S1 and the curcumin alcohol solution obtained in step S2 are mixed in a mass ratio of 3:(1-3) to obtain a mixed solution when the final ethanol concentration is 25-50% (v / v), the mixed solution is stirred for 0.5-2h, and then rotary evaporated under heating conditions of 40-60°C water bath, and when 50-80% of the initial volume of the mixed solution is distilled out, the distillation is stopped, and the distilled mixed solution is centrifuged at 6000-8000g for 10-20min, and the supernatant is collected to obtain a nanoparticle solution;

[0012] Step S4. Add a spinning aid to the nanoparticle solution obtained in step S3, stir evenly to obtain a spinning solution, and then electrospin the spinning solution to obtain.

[0013] Furthermore, the extraction method of beet pectin in step S1 is:

[0014] A. Wash, dry and crush the beet pulp, pass it through a 40-mesh sieve to obtain beet pulp powder, add water to the beet pulp powder and mix, the amount of water added is 15 to 50 times the mass of the beet pulp powder, then adjust the pH value to 1 to 3, extract it in a water bath at a temperature of 60 to 90°C for 1 to 3 hours, filter it, take the filtrate, and set aside the residue;

[0015] B. Rinse the filter residue of step A with clean water for 2 to 3 times, add water to mix, the amount of water added is 15 to 50 times the mass of the beet pulp powder in step A, then adjust the pH value to 11 to 13, extract in a water bath at a temperature of 60 to 90° C. for 1 to 3 hours, filter, and take the filtrate;

[0016] C. The filtrate obtained in step A is mixed evenly with the filtrate obtained in step B to obtain a mixed solution, and the pH value of the mixed solution is adjusted to 2-5, and then ethanol is added to make the concentration of ethanol in the mixed solution 40-50% (v / v), and the mixture is centrifuged at 8000-10000g for 10-30min, and the supernatant is collected. Subsequently, the ethanol concentration of the supernatant is adjusted to 70-80% (v / v), and the mixture is centrifuged at 8000-10000g for 10-30min, and the precipitate is collected. The precipitate is washed 2-3 times with 95% anhydrous ethanol, and dried at 40-50°C for 24h.

[0017] Furthermore, the concentration of beet pectin in the beet pectin solution in step S1 is 1 to 3 wt.%.

[0018] Furthermore, the concentration of curcumin in the curcumin alcohol solution in step S2 is 0.01-0.1 wt.%.

[0019] Furthermore, the amount of hesperetin added in step S2 is 20-50% of the quality of curcumin.

[0020] Furthermore, the spinning aid in step S4 is pullulan.

[0021] Furthermore, the mass ratio of the pullulan to the nanoparticle solution is (1.5-3):(7-8.5).

[0022] Furthermore, the conditions for electrospinning in step S4 are: temperature of 15-40°C, humidity of 20-60%, positive voltage of 15-20 kV, negative voltage of -15--20 kV, pump flow rate of 0.05-0.2 mL / h, round-trip distance of the nozzle of 90-130 mm, distance between the spinneret and the receiving plate of 12-16 cm, and receiving roller speed of 10-30 mm / s.

[0023] In addition, the present invention also seeks to protect the nanofiber cling film prepared by the preparation method of the nanofiber cling film.

[0024] Furthermore, the present invention also seeks to protect the use of the nanofiber cling film in the preservation of aquatic products.

[0025] The average diameter is an important parameter of nanofibers. After a lot of exploratory experiments, the inventors concluded that the average diameter of the nanofiber membrane is related to the particle size and uniformity of the nanoparticles in the spinning solution. The smaller the particle size of the nanoparticles used to prepare nanofibers and the more uniform the distribution, the smaller the average diameter of the prepared nanofibers, the fewer spindle-like structures, and the more uniform the properties. When the concentration of the beet pectin solution is 1-3wt.%, it is mixed with the curcumin alcohol solution containing hesperidin, stirred, and rotary evaporated to form a nanoparticle solution, the nanoparticle size of which is 493.5nm, PDI is less than 0.25, and has good particle size advantages and excellent dispersibility. The inventor then added pullulan to the nanoparticle solution as a spinning aid, and made the nanoparticle solution into a nanofiber membrane by electrospinning. The average diameter of the nanofiber membrane is 65.1nm, and the number of spindles in the nanofiber is small. The nanofiber can not only effectively improve the stability of curcumin and hesperidin under ultraviolet light, but also ensure the antioxidant and antibacterial effects of curcumin and hesperidin.

[0026] In addition, the inventor applied the nanofiber cling film as a cling film to the preservation of crispy grass carp. Experiments have shown that the nanofiber cling film has good water solubility. After being applied to the surface of the fish, it can quickly adhere to the surface of the fish. During storage, it can effectively inhibit the growth of microorganisms, slow down the decomposition rate of fish by endogenous enzymes and microorganisms, and reduce the degree of damage to the muscle fiber tissue of the fish. It can effectively maintain the elasticity, resilience, chewiness, adhesion, cohesion and hardness of the crispy grass carp meat, and maintain the unique taste of the crispy grass carp.

[0027] In summary, compared with the prior art, the nanofiber cling film provided by the present invention has the advantages of good encapsulation effect, good adhesion, high stability and significant antibacterial effect. The nanofiber cling film is used as a cling film in the preservation of crispy grass carp, which can effectively maintain the elasticity, resilience, chewiness, adhesion, cohesion and hardness of the crispy grass carp meat, maintain the unique taste of the crispy grass carp, and effectively extend the shelf life of the crispy grass carp. It is a relatively ideal natural crispy grass carp cling film. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are the appearance and microscopic morphology of nanoparticle solution and freeze-dried powder.

[0029] Figure 2 The appearance image, diameter distribution image and microscopic morphology images at magnifications of 2,000, 5,000 and 20,000 times of the nanofiber cling film prepared in Example 4 are shown.

[0030] Figure 3 This is a graph showing changes in pH value of fish during storage.

[0031] Figure 4 This is a graph showing changes in the volatile basic nitrogen (TVB-N) content of fish during storage.

[0032] Figure 5 This is a graph showing changes in the total bacterial count (TVC) of fish during storage.

[0033] Figure 6 This is a diagram showing the elasticity changes of fish meat during storage.

[0034] Figure 7 This is a diagram showing the recovery changes of fish meat during storage.

[0035] Figure 8 This is a graph showing the changes in the chewiness of fish during storage.

[0036] Fig. 9 This is a diagram showing the changes in the cohesion of fish meat during storage.

[0037] Fig.10 This is a diagram showing the changes in the adhesiveness of fish during storage.

[0038] Fig.11 This is a graph showing the changes in hardness of fish meat during storage.

[0039] Fig.12 This is a diagram showing the apparent changes in fish meat during storage. DETAILED DESCRIPTION

[0040] The present invention is further described below by describing specific embodiments, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention. The materials involved in the present invention are all food grade and can be obtained by commercial or conventional technical means in the art.

[0041] Embodiment 1, the extraction method of beet pectin:

[0042] A. Wash, dry and crush the beet pulp, pass it through a 40-mesh sieve to obtain beet pulp powder, add water to the beet pulp powder and mix, the amount of water added is 30 times the mass of the beet pulp powder, then adjust the pH value to 2, extract in a water bath at 75°C for 3 hours, filter, take the filtrate, and set aside the residue;

[0043] B. Rinse the filter residue of step A with clean water for 3 times, add water to mix, the amount of water added is 25 times the mass of the beet pulp powder in step A, then adjust the pH value to 12, extract for 3 hours in a water bath at a temperature of 75°C, filter, and take the filtrate;

[0044] C. The filtrate obtained in step A and the filtrate obtained in step B are mixed uniformly to obtain a mixed solution, and the pH value of the mixed solution is adjusted to 2-5, and then ethanol is added to make the concentration of ethanol in the mixed solution 45% (v / v), centrifuge at 10000g for 20 min, collect the supernatant, and then adjust the ethanol concentration of the supernatant to 75% (v / v), centrifuge at 10000g for 20 min, collect the precipitate, wash the precipitate 3 times with 95% anhydrous ethanol, and dry at 45°C for 24h.

[0045] Example 2: A method for preparing a nanofiber cling film

[0046] Step S1. Dissolve 1 g of the beet pectin prepared in Example 1 in 100 mL of distilled water and stir evenly to obtain a beet pectin solution with a concentration of 1 wt.%;

[0047] Step S2. Add 0.075 g of curcumin and 0.025 g of hesperetin into 100 mL of anhydrous ethanol and stir evenly to obtain a curcumin alcohol solution containing hesperetin, wherein the concentration of curcumin in the curcumin alcohol solution containing hesperetin is 0.075 wt.%, and the concentration of hesperetin is 0.025 wt.%;

[0048] Step S3. The beet pectin solution obtained in step S1 and the curcumin alcohol solution obtained in step S2 are mixed at a mass ratio of 3:2 to obtain a mixed solution when the final ethanol concentration is 40% (v / v). The mixed solution is placed on a magnetic stirrer and stirred for 1 hour to be fully mixed. The mixed solution is then placed on a rotary evaporator and subjected to rotary evaporation in a 45° C. water bath. When 50% of the initial volume of the mixed solution is distilled out, the distillation is stopped. The distilled mixed solution is centrifuged at 8000 g for 10 minutes, and the supernatant is collected to obtain a nanoparticle solution.

[0049] Step S4. Add pullulan to the nanoparticle solution obtained in step S3, wherein the mass ratio of pullulan to the nanoparticle solution is 1.5:8.5, stir evenly to obtain a spinning solution, and electrospin the spinning solution. The electrospinning conditions are as follows: temperature of 30°C, humidity of 20%, positive voltage of 20 kV, negative voltage of -20 kV, pump flow rate of 0.1 mL / h, round-trip distance of the nozzle of 130 mm, distance between the spinneret and the receiving plate of 16 cm, and speed of the receiving roller of 30 mm / s.

[0050] Example 3: A method for preparing a nanofiber cling film

[0051] Step S1. Dissolve 1.5 g of the beet pectin prepared in Example 1 in 100 mL of distilled water and stir evenly to obtain a beet pectin solution with a concentration of 1.5 wt.%;

[0052] Step S2. Add 0.05 g of curcumin and 0.02 g of hesperetin into 100 mL of anhydrous ethanol and stir evenly to obtain a curcumin alcohol solution containing hesperetin, wherein the concentration of curcumin in the curcumin alcohol solution containing hesperetin is 0.05 wt.%, and the concentration of hesperetin is 0.02 wt.%;

[0053] Step S3. The beet pectin solution obtained in step S1 and the curcumin alcohol solution obtained in step S2 are mixed at a mass ratio of 1:1 to obtain a mixed solution when the final ethanol concentration is 50% (v / v). The mixed solution is placed on a magnetic stirrer and stirred for 1 hour to be fully mixed. The mixed solution is then placed on a rotary evaporator and subjected to rotary evaporation in a 40° C. water bath. When 80% of the initial volume of the mixed solution is distilled out, the distillation is stopped. The distilled mixed solution is centrifuged at 6000 g for 20 minutes, and the supernatant is collected to obtain a nanoparticle solution.

[0054] Step S4. Add pullulan to the nanoparticle solution obtained in step S3, wherein the mass ratio of pullulan to the nanoparticle solution is 1:3, stir evenly to obtain a spinning solution, and electrospin the spinning solution. The electrospinning conditions are as follows: temperature of 35°C, humidity of 60%, positive voltage of 15kV, negative voltage of -15kV, pump flow rate of 0.15mL / h, round-trip distance of the nozzle of 130mm, distance between the spinneret and the receiving plate of 12cm, and speed of the receiving roller of 30mm / s.

[0055] Example 4: Preparation method of nanofiber cling film

[0056] Step S1. Dissolve 3 g of the beet pectin prepared in Example 1 in 100 mL of distilled water and stir evenly to obtain a beet pectin solution with a concentration of 3 wt.%;

[0057] Step S2. adding 0.1 g and 0.04 g of hesperetin to 100 mL of anhydrous ethanol and stirring evenly to obtain a curcumin alcohol solution containing hesperetin, wherein the concentration of curcumin in the curcumin alcohol solution containing hesperetin is 0.1 wt.%, and the concentration of hesperetin is 0.04 wt.%;

[0058] Step S3. The beet pectin solution obtained in step S1 and the curcumin alcohol solution obtained in step S2 are mixed at a mass ratio of 3:1 to obtain a mixed solution when the final ethanol concentration is 25% (v / v). The mixed solution is placed on a magnetic stirrer and stirred for 2 hours to be fully mixed. The mixed solution is then placed on a rotary evaporator and subjected to rotary evaporation in a 55° C. water bath. When 50% of the initial volume of the mixed solution is distilled out, the distillation is stopped. The distilled mixed solution is centrifuged at 7000 g for 15 minutes, and the supernatant is collected to obtain a nanoparticle solution.

[0059] Step S4. Add pullulan to the nanoparticle solution obtained in step S3, wherein the mass ratio of pullulan to the nanoparticle solution is 1:4, stir evenly to obtain a spinning solution, and electrospin the spinning solution. The electrospinning conditions are as follows: temperature of 32°C, humidity of 40%, positive voltage of 18kV, negative voltage of -18kV, pump flow rate of 0.2mL / h, round-trip distance of the nozzle of 130mm, distance between the spinneret and the receiving plate of 14cm, and speed of the receiving roller of 30mm / s.

[0060] Experimental Example 1: Physical and Chemical Properties of Curcumin Nanoparticle Solution

[0061] 1. Experimental materials:

[0062] The nanoparticle solution prepared in step S3 of Example 4.

[0063] 2. Experimental methods:

[0064] Determine the diameter potential of the nanoparticle solution obtained in step S3 of Example 4 and observe the particle size distribution of the nanoparticle solution. Wherein: the measurement of particle size and potential refers to the research of Mariano et al. (Mariano, A., Li, YO, Singh, H., McClements, DJ, & Davidov-Pardo, G. (2024). Encapsulation of orange-derived hesperetin inzein / pectin nanoparticles: Fabrication, characterization, stability, and bioaccessibility. Food Hydrocolloids, 153, 110024.), and use Malvern nanoparticle sizer (Zetasizer Nano ZS 90) to measure the particle size and distribution of the nanoparticle solution droplets. The specific operation is as follows: the nanoparticle solution is diluted with deionized water to 2 mg / mL (calculated based on the concentration of pectin in the nanoparticle solution), and 1 mL of the diluent is added to the sample cell of the nanoparticle sizer to determine the average particle size. The sample dilution operation of the potential test is consistent with the sample dilution operation of the particle size test mentioned above. Take 1 mL of the diluted nanoparticle solution sample and place it in the potential cell for measurement. The test temperature is 25°C, the instrument equilibrium time before sample measurement is 120s, each sample is measured 3 times, and each group of samples is measured three times. The microstructure of the nanoparticle solution is observed by field emission scanning electron microscopy (SEM) at a voltage of 10kV.

[0065] 3. Experimental results:

[0066] The experimental results are shown in Table 1 and Figure 1 shown.

[0067] 3.1. The particle size, zeta potential, PDI and potential value of the nanoparticles are shown in Table 1:

[0068] Table 1 Particle size, zeta potential, PDI and potential value of nanoparticle solution

[0069] Sample name Particle size (nm) PDI Potential (mV) Nanoparticles 493.5±5.36 0.24±0.06 -25.83±0.76

[0070] 3.2 Appearance and microscopic morphology of nanoparticle solution and freeze-dried powder Figure 1 As shown, Figure 1 -A is the appearance morphology of the nanoparticle solution, Figure 1 -B is the appearance of the freeze-dried powder of nanoparticle solution, Figure 1 -C is the microscopic morphology of the freeze-dried nanoparticle powder under scanning electron microscope.

[0071] Depend on Figure 1As shown in Table 1, the freshly prepared nanoparticle solution of Example 4 is a yellow-brown translucent solution under naked eye observation, without obvious precipitation and stratification. After the nanoparticles are freeze-dried into powder, they appear yellow-brown sponge-like, and electron microscopic observation shows that they have a network structure. The particle size of the nanoparticles is 493.5nm, and the PDI is less than 0.25, indicating that the nanoparticle solution has a small particle size and good dispersibility.

[0072] Experimental Example 2: Scanning Electron Microscope Analysis of Nanofiber Cling Film

[0073] 1. Experimental materials:

[0074] The nanofiber cling film prepared in Example 4.

[0075] 2. Experimental methods:

[0076] A small sample with an area of ​​5 mm × 5 mm was cut from the nanofiber cling film prepared in Example 4. After gold spraying, the microscopic morphology of the nanofibers was observed by SEM at a voltage of 10 kV. The diameters of different nanofibers were measured using Image J software. 30 fibers were randomly selected from each group (excluding agglomerates). The arithmetic mean and error value of 3 groups were calculated, and their diameter distribution was analyzed.

[0077] 3. Experimental results:

[0078] The experimental results are as follows Figure 2 As shown, Figure 2 Figure A is the appearance of the nanofiber cling film prepared in Example 4, Figure B is the diameter distribution diagram of the nanofiber cling film prepared in Example 4, and Figures C, D and E are microscopic morphology diagrams of the nanofiber cling film prepared in Example 4 under scanning electron microscope observation at magnifications of 2,000, 5,000 and 20,000 times.

[0079] The nanofiber cling film was observed by electron microscope at magnifications of 2 000 times, 5 000 times and 20 000 times. Figure 2 It can be seen that the nanofiber cling film prepared with pullulan as a spinning aid presents a porous three-dimensional network structure. Under high-power lens observation, it can be found that the surface of the nanofiber is smooth with very few protrusions. This protrusion-like structure is significantly less and smaller than the nanoparticles, which indicates that the nanoparticles are successfully encapsulated during the electrospinning process. Image J was used to analyze the diameter of the nanofiber cling film. The results showed that the average diameter of the nanofiber cling film prepared in Example 4 was 65.1nm, mainly distributed between 50 and 80nm, which was significantly smaller than the particle size of the nanoparticles. This shows that the electrospinning process effectively stretched the nanoparticles and the structure was further nanosized.

[0080] Experimental Example 3: Antioxidant Stability of Nanofibers under UV Light

[0081] 1. Experimental materials:

[0082] The nanoparticle solution prepared in step S3 of Example 4 and the nanofiber cling film prepared in Example 4.

[0083] 2. Experimental methods:

[0084] The antioxidant stability of the nanoparticle solution prepared in step S3 of Example 4 and the nanofiber cling film prepared in Example 4 after ultraviolet light treatment was measured.

[0085] 2.1. Determination of the antioxidant stability of nanoparticle solution under ultraviolet light:

[0086] (1) ABTS free radical scavenging experiment of nanoparticle solution The method of Xu et al. (Xu, PW, Yue, XJ, Yuan, XF, & Zhao, B. (2024). Hemp seed globulin-alginate nanoparticles for encapsulation of Cannabisin A with enhanced colloidal stability and antioxidant activity. International Journal of Biological Macromolecules, 256, 128380) was referred to and partially modified. The detailed operation is as follows: 7 mmol / L ABTS aqueous solution and 2.45 mmol / L potassium persulfate aqueous solution were prepared with distilled water, and the two were mixed to obtain the ABTS solution required for the test. The solution was stored in the dark for 12 h at room temperature and diluted with deionized water before use to make its absorbance at 0.7±0.05. Then, the sample and ABTS solution were mixed evenly in a ratio of 1:4, and the reaction was shaken for 30 min in the dark, and then the absorbance was measured at 734 nm using an automatic microplate reader; deionized water replaced the ABTS solution as a blank. The samples were diluted 100 times with deionized water before the experiment.

[0087]

[0088] Where:

[0089] R1--ABTS free radical scavenging rate, %;

[0090] A1--absorbance value of nanoparticle solution sample;

[0091] A0--absorbance value of blank sample.

[0092] (2) The DPPH free radical scavenging experiment of nanoparticle solution was based on the method of Xu et al. (Xu, PW, Yue, XJ, Yuan, XF, & Zhao, B. (2024). Hemp seed globulin-alginate nanoparticles for encapsulation of Cannabisin A with enhanced colloidal stability and antioxidant activity. International Journal of Biological Macromolecules, 256, 128380.), and some modifications were made. The specific operation is as follows: Weigh an appropriate amount of DPPH powder to make a 0.2mmol / L DPPH ethanol solution, store it in a light-proof environment for 2 hours, and use it after it stabilizes. Take 3mL of nanoparticle solution and 1mL of DPPH ethanol solution and mix them evenly, and oscillate the reaction in a light-proof environment for 30 minutes. Then centrifuge and take the supernatant to measure its absorbance value at 517nm using an automatic microplate reader. The calculation formula is as follows:

[0093]

[0094] Where:

[0095] R2--DPPH clearance rate, %;

[0096] A2--the absorbance value of the sample plus DPPH alcohol solution;

[0097] A1--the absorbance value of the sample plus ethanol;

[0098] A0--The absorbance value of DPPH plus ethanol.

[0099] 2.2. Determination of the antioxidant activity of nanofiber cling film:

[0100] The antioxidant activity of the nanofiber cling film was determined by DPPH and ABTS free radical scavenging experiments. The method was based on the research of Liu et al. (Liu, Y., Xia, X., Li, X., Wang, F., Huang, Y., Zhu, B., Feng, X., & Wang, Y. (2024). Design and characterization of edible chitooligosaccharide / fish skin gelatinnanofiber-based hydrogel with antibacterial and antioxidant characteristics. International Journal of Biological Macromolecules, 130033.) and appropriate modifications were made. The specific operation was as follows: the nanofiber cling film was dissolved in distilled water to prepare a 100 mg / mL membrane solution. Subsequently, 3 mL of 0.1 mmol / L DPPH ethanol solution and 3 mL of the membrane solution were oscillated in the dark for 30 minutes. After centrifugation, the supernatant was taken and the absorbance was measured at 517 nm. The ABTS free radical scavenging experiment was similar to that of DPPH. 4 mL of ABTS working solution and 4 mL of membrane solution were reacted for 10 min. After centrifugation, the supernatant was taken and the absorbance was measured at 734 nm.

[0101]

[0102] Where:

[0103] R3--free radical scavenging rate of nanofiber cling film, %;

[0104] A0--absorbance value of blank control;

[0105] A1--The absorbance value of nanofiber cling film for free radical scavenging.

[0106] 2.3 Antioxidant stability of nanoparticle solution and nanofiber membrane under UV irradiation:

[0107] The antioxidant test method of the samples under ultraviolet light is the same as 2.1 and 2.2. The specific operation is as follows: the nanoparticle solution and the nanofiber membrane are irradiated under ultraviolet light (20W) for 6 hours, and samples are taken every 2 hours to detect the antioxidant activity of the samples.

[0108] 3. Experimental results:

[0109] The experimental results are shown in Table 2.

[0110] Table 2 ABTS and DPPH free radical scavenging rates

[0111]

[0112] Note: Different lowercase letters on the right shoulder of the same column indicate significant differences (p<0.05). SCH is the nanoparticle solution prepared in step S3 of Example 4, and P-SCH is the nanofiber cling film prepared in Example 4.

[0113] As shown in Table 2, the ABTS removal rate of the freshly prepared nanoparticle solution is 63.2%, and the DPPH removal rate is 81.3%. After the nanoparticle solution is spun into a nanofiber membrane by electrospinning, the ABTS removal rate of the nanofiber membrane is 61.5%, and the DPPT removal rate is 85.2%. The nanoparticle solution and the nanofiber membrane were placed under ultraviolet light for 6 hours. The results showed that after 6 hours of ultraviolet light irradiation, the scavenging rate of the nanoparticle solution for ABTS free radicals decreased to 47.7% (p < 0.05), and the scavenging rate for DPPH free radicals decreased to 57.4% (p < 0.05). These results show that the nanoparticle solution has a poor resistance to ultraviolet light. However, the nanofiber membrane made of the nanoparticle solution and placed under ultraviolet light for 6 hours had no significant effect on the scavenging ability of ABTS and DPPH free radicals (p > 0.05), which shows that the nanofiber membrane has a certain shielding effect on ultraviolet light and can protect the active substances encapsulated inside the fiber.

[0114] Experimental Example 4: Application of Nanofiber Fresh-keeping Film in Fish Preservation

[0115] 1. Experimental materials:

[0116] The nanofiber cling film prepared in Example 4.

[0117] 2. Experimental methods:

[0118] 2.1. Fish processing and sample preparation:

[0119] Fresh crispy carp was purchased from a supermarket, and the head, scales and internal organs were removed. After washing, the back meat of the fish was cut into 5.0-6.0 g fish slices, and then rinsed with sterile water for 2-3 times, and then rinsed with 75% ethanol for 2-3 times and then rinsed with distilled water to remove the residual ethanol in the fish. Then, the crispy carp slices were soaked for 10 min (control group) and applied externally (treatment group) with physiological saline (control group) and nanofiber preservative film prepared in Example 4 (treatment group), respectively. After the fish in the control group was soaked, it was packaged in a sterile self-sealing bag, and the treatment group was packaged in a sterile self-sealing bag after the nanofiber film completely covered the surface of the fish and tightly fitted. Both groups of fish were stored at 4 ° C, and fish samples were taken regularly (0d, 2d, 4d, 6d, 8d) for pH, TVB-N, total colony count and fish texture detection.

[0120] 2.2. pH determination of fish meat:

[0121] Accurately weigh 5.0 g of the sample to be tested, chop it with a sterile blade on a sterile operating table, then add 50 mL of deionized water and homogenize at high speed to fully break the fish meat. Then, centrifuge at 10,000 g and 4°C for 5 minutes, take the supernatant, and measure the pH value of the sample with a pH meter.

[0122] 2.3、Fish TVB-N Determination:

[0123] The content of TVB-N in fish meat was tested according to the Kjeldahl method in GB 5009.228-2016. The content of volatile basic nitrogen in the sample was calculated according to the following formula:

[0124]

[0125] Where:

[0126] V1--the volume of hydrochloric acid standard solution consumed by the sample solution, mL;

[0127] V2--the volume of blank consumed hydrochloric acid standard solution, mL;

[0128] C--Concentration of hydrochloric acid standard solution, mol / L;

[0129] m--sample mass, g;

[0130] 14--Titrate 1.0mL of hydrochloric acid (c(HCl) = 1.000mol / L) or sulfuric acid (c(H2SO4) = 1.000mol / L) standard solution to determine the nitrogen content of the solution in grams per mole (g / mol).

[0131] 2.4. Counting of total colony count:

[0132] Mix 5.0g of fish sample with 45mL of sterilized saline solution, then add it to a sterile homogenizer bag and beat it for 2 minutes at 8000rpm / min. Take the homogenized solution and dilute it 10 times continuously. Take 1mL of each gradient solution and transfer it to a culture dish, then pour in the appropriate culture medium. After solidification, turn the culture medium upside down and place it in a 30℃ incubator for 3 days, and finally count it. The culture medium used to calculate the total number of colonies is plate count agar. The unit of microorganisms is log 10 CFU / g.

[0133] 2.5. Fish meat texture determination:

[0134] The texture characteristics of fish fillets were measured by a physical property analyzer equipped with a P 0.5 probe. All fish samples were cut into rectangular slices of 1.5 cm × 1.5 cm × 1.0 cm (5.0 g) and placed on ice before the experiment. The samples were compressed to 50% deformation at a test speed of 3, 1, and 1 mm / s and a trigger force of 5.0 g before, during, and after the experiment, respectively, to measure the springiness, resilience, chewiness, cohesiveness, gumminess, and hardness of the fish.

[0135] 3. Experimental results:

[0136] 3.1. The results of fish meat pH determination are shown in Table 3 and Figure 3 As shown:

[0137] Table 3 Fish pH measurement results

[0138] Storage time Control group Treatment Group 0 <![CDATA[6.18±0.05 Ac ]]> <![CDATA[6.18±0.05 Ab ]]> 2 <![CDATA[6.24±0.08 Ac ]]> <![CDATA[6.18±0.08 Ab ]]> 4 <![CDATA[6.16±0.11 Ac ]]> <![CDATA[6.05±0.09 Ba ]]> 6 <![CDATA[6.63±0.15 Ab ]]> <![CDATA[6.19±0.11 Bb ]]> 8 <![CDATA[6.87±0.17 Aa ]]> <![CDATA[6.17±0.08 Bb ]]>

[0139] Note: Different capital letters in the same row indicate significant differences between groups (p<0.05), and different lowercase letters in the same column indicate significant differences within groups (p<0.05).

[0140] The change of pH value is one of the important indicators for evaluating the spoilage of aquatic products. The pH changes of fish meat in each group during storage are shown in Table 3 and Figure 3 As shown. In the early stage of storage (0 to 4 days), the pH value of fish meat began to drop from 6.18 to 6.16 and 6.05, respectively. This was due to the degradation of glycogen in the fish meat to produce lactic acid in the early stage of storage. In the later stage of storage, 4 to 8 days, alkaline compounds such as ammonia and trimethylamine were produced due to the action of microorganisms and endogenous enzymes, which increased the overall pH value of fish meat. Compared with the control group, the pH change in the treatment group increased more slowly, indicating that the number of alkaline compounds such as ammonia that caused the pH increase was reduced, because the nanofiber membrane in the treatment group inhibited the protein decomposition caused by microorganisms.

[0141] 3.2. The results of fish meat TVB-N determination are shown in Table 4 and Figure 4 As shown:

[0142] Table 4 Fish meat TVB-N determination results

[0143] Storage time Control group (mg / 100g) Treatment group (mg / 100g) 0 <![CDATA[9.43±0.18 Ae ]]> <![CDATA[9.43±0.18 Ab ]]> 2 <![CDATA[10.42±0.26 Ad ]]> <![CDATA[10.17±0.31 Ab ]]> 4 <![CDATA[14.22±0.46 Ac ]]> <![CDATA[11.48±0.34 Cb ]]> 6 <![CDATA[25.89±0.62 Ab ]]> <![CDATA[15.54±0.58 Ba ]]> 8 <![CDATA[41.65±0.67 Aa ]]> <![CDATA[19.21±0.56 Ca ]]>

[0144] Note: Different capital letters in the same row indicate significant differences between groups (p<0.05), and different lowercase letters in the same column indicate significant differences within groups (p<0.05).

[0145] From Table 4 and Figure 4 It can be seen that the TVB-N value and growth rate of the treatment group are lower than those of the control group. On the 4th day of storage, the TVB-N values ​​of the control group and the treatment group were kept within the first-level freshness level (15mg / 100g), but on the 6th day, the control group exceeded the second-level freshness level (20mg / 100g), at which time the meat had become corrupt and inedible. The treatment group was close to the second-level freshness level on the 8th day, indicating that the treatment group can inhibit the production of TVB-N in fish meat and achieve a freshness-preserving effect.

[0146] 3.3. The results of the total colony counts in fish meat are shown in Table 5 and Figure 5 As shown:

[0147] Table 5 Counting results of total colony counts in fish meat

[0148] Storage time <![CDATA[Control group (log 10 CFU / g)]]> <![CDATA[Treatment group (log 10 CFU / g)]]> 0 <![CDATA[5.22±0.1 Ae ]]> <![CDATA[5.22±0.1 Ac ]]> 2 <![CDATA[5.48±0.07 Ad ]]> <![CDATA[5.23±0.1 Ac ]]> 4 <![CDATA[6.05±0.17 Ac ]]> <![CDATA[5.43±0.15 Bc ]]> 6 <![CDATA[7.28±0.33 Ab ]]> <![CDATA[6.09±0.24 Bb ]]> 8 <![CDATA[8.51±0.38 Aa ]]> <![CDATA[6.56±0.23 Ba ]]>

[0149] Note: Different capital letters in the same row indicate significant differences between groups (p<0.05), and different lowercase letters in the same column indicate significant differences within groups (p<0.05).

[0150] From Table 5 and Figure 5 It can be seen that the total number of colonies in the fish meat of the treatment group after the fourth day of storage was significantly lower than that of the control group fish meat during the same storage period (p<0.05), indicating that the nanofiber membrane can effectively inhibit the growth of microorganisms in fish meat during storage.

[0151] 3.4. The results of fish meat texture determination are shown in Tables 6 and Figure 6 to Figure 11 As shown:

[0152] Table 6 Results of fish texture determination

[0153]

[0154] Note: Different capital letters in the same column indicate significant differences between groups (p<0.05), and different lowercase letters in the same row indicate significant differences within groups (p<0.05).

[0155] From Table 6 and Figure 6 to Figure 11 It can be seen that during the entire storage period, due to the autolysis of fish muscle after death, the endogenous enzymes in the fish meat will cause protein degradation and fibrous tissue will be destroyed. From the data of various indicators, all values ​​are declining, and the degree of decline in the treatment group is lower than that in the control group. This is because the nanofiber cling film plays a role in inhibiting enzyme decomposition or inhibiting the destruction of fibrous tissue. Fig.12It can be seen that fresh fish meat is white and has a certain hardness. After 8 days of storage, the fish meat in the treatment group has no obvious odor, and the appearance has hardly changed. No obvious signs of corruption are observed. However, a clear odor can be smelled in the control group, and the appearance is obviously dark yellow, and obvious corruption can be observed.

[0156] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a nanofiber cling film, characterized in that: The following steps are involved: Step S1. dissolving beet pectin in distilled water and stirring to obtain a beet pectin solution; Step S2. Add curcumin and hesperetin into anhydrous ethanol and stir evenly to obtain a curcumin alcohol solution containing hesperetin; Step S3. The beet pectin solution obtained in step S1 and the curcumin alcohol solution obtained in step S2 are mixed in a mass ratio of 3:(1-3) to obtain a mixed solution when the final ethanol concentration is 25-50% (v / v), the mixed solution is stirred for 0.5-2h, and then rotary evaporated under heating conditions of 40-60°C water bath, and when 50-80% of the initial volume of the mixed solution is distilled out, the distillation is stopped, and the distilled mixed solution is centrifuged at 6000-8000g for 10-20min, and the supernatant is collected to obtain a nanoparticle solution; Step S4. Adding a spinning aid to the nanoparticle solution obtained in step S3, stirring evenly to obtain a spinning solution, and then subjecting the spinning solution to electrospinning to obtain; The extraction method of beet pectin in step S1 is: A. Wash, dry and crush the beet pulp, pass it through a 40-mesh sieve to obtain beet pulp powder, add water to the beet pulp powder and mix, the amount of water added is 15 to 50 times the mass of the beet pulp powder, then adjust the pH value to 1 to 3, extract it in a water bath at a temperature of 60 to 90°C for 1 to 3 hours, filter it, take the filtrate, and set aside the residue; B. Rinse the filter residue of step A with clean water for 2 to 3 times, add water to mix, the amount of water added is 15 to 50 times the mass of the beet pulp powder in step A, then adjust the pH value to 11 to 13, extract in a water bath at a temperature of 60 to 90° C. for 1 to 3 hours, filter, and take the filtrate; C. The filtrate obtained in step A is mixed evenly with the filtrate obtained in step B to obtain a mixed solution, and the pH value of the mixed solution is adjusted to 2-5, and then ethanol is added to make the concentration of ethanol in the mixed solution 40-50% (v / v), and the mixture is centrifuged at 8000-10000g for 10-30min, and the supernatant is collected. Subsequently, the ethanol concentration of the supernatant is adjusted to 70-80% (v / v), and the mixture is centrifuged at 8000-10000g for 10-30min, and the precipitate is collected. The precipitate is washed 2-3 times with 95% anhydrous ethanol, and dried at 40-50°C for 24h.

2. The method for preparing the nanofiber cling film according to claim 1, characterized in that: The concentration of beet pectin in the beet pectin solution in step S1 is 1-3 wt.%.

3. The method for preparing the nanofiber cling film according to claim 1, characterized in that: The concentration of curcumin in the curcumin alcohol solution in step S2 is 0.01-0.1 wt.%.

4. The method for preparing the nanofiber cling film according to claim 1, characterized in that: The amount of hesperidin added in step S2 is 20-50% of the quality of curcumin.

5. The method for preparing the nanofiber cling film according to claim 1, characterized in that: The spinning aid in step S4 is pullulan.

6. The method for preparing the nanofiber cling film according to claim 5, characterized in that: The mass ratio of the pullulan to the nanoparticle solution is (1.5-3):(7-8.5).

7. The method for preparing the nanofiber cling film according to claim 1, characterized in that: The conditions for electrospinning in step S4 are: temperature of 15-40°C, humidity of 20-60%, positive voltage of 15-20kV, negative voltage of -15--20kV, pump flow rate of 0.05-0.2mL / h, round-trip distance of the nozzle of 90-130mm, distance between the spinneret and the receiving plate of 12-16cm, and receiving roller speed of 10-30mm / s.

8. The nanofiber cling film obtained by the method for preparing the nanofiber cling film according to any one of claims 1 to 7.

9. Use of the nanofiber cling film as claimed in claim 8 in the preservation of aquatic products.

Citation Information

Patent Citations

  • Oxidation-resistant cellulose acetate nano fibrous preservative film for food

    CN106757464A

  • Preparation method of edible nanofiber preservative film

    CN106966047A

  • Composite nano fiber fresh-keeping film preparation and application thereof

    CN108049027A

  • A kind of multi-functional preservation film for meat products and its application

    AU2021101023A4

  • Nano-essential oil emulsion and application in fresh keeping of fresh-cut fruits and vegetables

    CN108925626A